Resilience and Entrepreneurial Intention in Peruvian Workers: Mediating Role of Transformational Leadership - Ortiz Ramirez, Jean A. (2021)
The general objective of this study was to evaluate and discuss the mediating role of transformational leadership between the association of resilience and entrepreneurial intention in peruvian adults. A total of 199 adults, 96 (48%) women and 103 (52%) men, aged between 18 and 50 years (M = 24, SD = 6.94) participated in this research. The psychometric properties of the instruments were evaluated, obtaining appropriate values corresponding to the evidence of validity based on internal structure (by means of AFC) and reliability (by means of the internal consistency method, alpha and omega coefficient). The level of Transformational Leadership was assessed with the MLQ-5X multifactor questionnaire, resilience was assessed with the Connor-Davidson Resilience scale and, finally, entrepreneurial intention was assessed with the Entrepreneurial Intention Questionnaire. The results corroborate that from the estimation of the mediating effect of Transformational Leadership between resilience and entrepreneurial intention the results obtained represented 71.1% mediation. The direct effect of resilience on entrepreneurial intention was not statistically significant (p = .169, 28.9%). In conclusion, transformational leadership plays a complete mediating role, as the main impact on the entrepreneurial intention variable. Finally, there is evidence of a predominant strength of transformational leadership as a mediating variable.